Compreensão ativa e relações dialógicas na leitura de poemas de Jenyffer Nascimento - Souza, Hugo Hudsney Santana de (2024)
Reading poetry, in traditional practices, often focuses on its formal aspect to the detriment of its content. The lack of a critical and dialogic approach to teaching poetry results in a limited understanding of this literary genre and neglect of the analysis of its axiological aspects. We propose an approach with ethical-discursive reading of poems, focusing on the book Terra Fértil, by poet Jenyffer Nascimento. Our research is based on the theories of language and understanding of poetry in Bakhtin (1998, 2003, 2010) and Voloshinov (2017, 2019), highlighting the categories: active understanding, dialogical relationships, value centers, author-person, author- creator, hero/character and author-contemplator. To carry out a process of didactic transposition of Bakhtin's circle categories, we rely on the studies of Carvalho (2021, p. 163) who points to didactic procedures in terms of reading from an ethical, aesthetic and discursive point of view with a focus on the domain of dialogic reading skills. Therefore, we applied and tested these procedures in a case study in this pilot study in order to report a reading experience with a poem with valued reframing. Based on the experience of didactic transposition of the Bakhtin Circle categories used by Carvalho (2023), we explored the procedures of dialogical reading in the field of practice in the classroom. In view of this study, we ultimately propose the production of a pedagogical notebook with activities aimed at students in the 9th year of elementary school.